2020
DOI: 10.1371/journal.pone.0230215
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factors for drug-related problems in a general hospital: A large prospective cohort

Abstract: Objective To identify risk factors for potential Drug-Related Problems (DRP) at admission in hospitalized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
(43 reference statements)
2
15
0
7
Order By: Relevance
“…When DRPs are not recognized and/or resolved, patients may experience treatment failure, adverse events, sub-optimal quality of life, and facing new medical conditions as well as mortality [ 3 , 6 , 7 ]. Furthermore, problems involving medication are associated with emergency department visits, extended hospitalizations, additional visits to the physician’s office, and additional prescriptions [ 8 , 9 ]. Overall, medication-related morbidity accounts for 7.0% of hospitalizations and has led to unnecessary health care expenditures in billions of dollars [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…When DRPs are not recognized and/or resolved, patients may experience treatment failure, adverse events, sub-optimal quality of life, and facing new medical conditions as well as mortality [ 3 , 6 , 7 ]. Furthermore, problems involving medication are associated with emergency department visits, extended hospitalizations, additional visits to the physician’s office, and additional prescriptions [ 8 , 9 ]. Overall, medication-related morbidity accounts for 7.0% of hospitalizations and has led to unnecessary health care expenditures in billions of dollars [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the results of the previous studies that CKD severity and medication errors are associated with medication-related problems [ 30 , 31 ]. However, well-known risk factors for DRPs, such as polypharmacy and comorbidity, were not significantly associated with DRPs in this study, possibly owing to the relatively small sample size and the propensity of bias towards patients with CKD stage 5 with high medication burdens and complicated comorbidity conditions [ 32 , 33 ]. The present study demonstrated that clinical pharmacist interventions significantly reduced the number of DRPs at discharge compared with usual care.…”
Section: Discussionmentioning
confidence: 98%
“…As expected, our findings highlighted that home-dwelling geriatric inpatients do not always return home after hospital discharge. This can be interpreted not only via the progression of the pathological processes leading to hospitalization but also through shared risk factors that lead to a downward spiral of accumulated adverse events and irreversible health outcomes in hospital [ 11 , 13 ]. In a previous study examining the same population, we explored institutionalization after hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Geriatric inpatients are susceptible to greater functional decline and adverse health events which are not directly related to the illness for which they were hospitalized [ 11 , 14 , 15 ]. Additionally, they are at risk of not being able to return to their homes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation